Effect of plasma rotation on the resonance magnetic perturbations at the edge of tokamak plasmas - Pankratov, I.M.; Pavlenko, I.V.; Pomazan, O.A.; Omelchenko, A.Ya. (Вопросы атомной науки и техники, 2012)
In the frame of one-fluid MHD the pressure perturbation resonant excitation by external low frequency helical magnetic perturbations near the plasma edge is investigated. The plasma rotation plays a key role in this phenomenon. The plasma response has been taken into account. These pressure perturbations may affect stability of the ballooning and peeling modes.